2021
DOI: 10.1136/bmj-2021-066306
|View full text |Cite
|
Sign up to set email alerts
|

Timing of dialysis initiation to reduce mortality and cardiovascular events in advanced chronic kidney disease: nationwide cohort study

Abstract: Objective To identify the optimal estimated glomerular filtration rate (eGFR) at which to initiate dialysis in people with advanced chronic kidney disease. Design Nationwide observational cohort study. Setting National Swedish Renal Registry of patients referred to nephrologists. Participants Patients had a baseline eGFR between 10 and 20 mL/min/1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 65 publications
(137 reference statements)
1
61
0
3
Order By: Relevance
“…It has been suggested that this is due to patients with high comorbidity starting dialysis at a higher eGFR [ 42 ] or that eGFR is artificially raised in cachectic patients with a low muscle mass [ 43 ]. Altogether these observations are in accordance with the IDEAL study [ 44 ], a randomized controlled trial which found no difference between early and late DI while in a study in Swedish dialysis patients very early initiation of dialysis was reported to be associated with a modest reduction in mortality and cardiovascular events in Swedish dialysis patients [ 45 ]. Our study thus suggests that DI should primarily be based on clinical rather than biochemical indications, with particular attention paid to patients with a rapid loss of renal function, which may lead to suboptimal DI [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
“…It has been suggested that this is due to patients with high comorbidity starting dialysis at a higher eGFR [ 42 ] or that eGFR is artificially raised in cachectic patients with a low muscle mass [ 43 ]. Altogether these observations are in accordance with the IDEAL study [ 44 ], a randomized controlled trial which found no difference between early and late DI while in a study in Swedish dialysis patients very early initiation of dialysis was reported to be associated with a modest reduction in mortality and cardiovascular events in Swedish dialysis patients [ 45 ]. Our study thus suggests that DI should primarily be based on clinical rather than biochemical indications, with particular attention paid to patients with a rapid loss of renal function, which may lead to suboptimal DI [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our present systematic review included 13 studies of the last ve years which investigated optimal dialysis initiation in ESKD patients, 9 of the 13 studies mainly focused on the optimal GFR of maintenance dialysis initiation; 7 studies used eGFR [9,11,13,14,16,18,20], 1 study used mGFR [8], 1 study used both [10]. Compared to previous studies, wider range of GFR values and more detailed data strati cation were applied in the study design and data processing stages; 7 studies[8, 10,13,14,16,20] taken GFR ≤ 5 mL/min/1.73 m2 or even lower into account, the lowest data range was mGFR < 4.3 mL/min/1.73m2 [10] and the highest range was eGFR 15-16 mL/min/1.73 m2 [13]. 5 studies [9,10,11,14,16] showed none association between GFR and mortality or other adverse outcomes, 2 studies [18,20] showed dialysis initiation at higher GFR levels were with poor prognosis, and 2 studies [8, 13] showed higher GFR levels with better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The study about urgent vs. early-start peritoneal dialysis by Silva et al [15] was the one study that did not use Cox regression and used rst 30-day complications, 6-month hospitalization events and 6-month dropout as outcomes. The nationwide cohort study from Sweden was the one study which estimated the effect of each dialysis initiation strategy on ve year all-cause mortality and major adverse cardiovascular events by using a weighted pooled logistic regression model [13]. Based on quality assessment scores, the Newcastle-Ottawa score of these 13 studies was 6 to 7.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…In an observational cohort study, very early initiation of dialysis at an estimated glomerular filtration rate of 15-16 ml/min per 1.73 m 2 was associated with a modest reduction in mortality and cardiovascular events as compared with dialysis initiation at an estimated glomerular filtration rate of 6-7 ml/min per 1.73 m 2 . 6 This reduction corresponded to a mean delay of death of 1.6 months over 5 years of follow-up, but dialysis would need to be started 4 years earlier.…”
Section: The Patient Perspectivementioning
confidence: 99%